2013
DOI: 10.3390/w5030945
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Watershed-Wildfire Risks on National Forest System Lands in the Rocky Mountain Region of the United States

Abstract: Abstract:Wildfires can cause significant negative impacts to water quality with resultant consequences for the environment and human health and safety, as well as incurring substantial rehabilitation and water treatment costs. In this paper we will illustrate how state-of-the-art wildfire simulation modeling and geospatial risk assessment methods can be brought to bear to identify and prioritize at-risk watersheds for risk mitigation treatments, in both pre-fire and post-fire planning contexts. Risk assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…For each case, the choice of contaminant(s) of concern and potential impacts constrain the possible approaches for post‐fire contamination assessment, and therefore, they should be identified at the outset. Recent studies have focused on determining the sensitivity to post‐fire contamination and range from relatively simple spatial indices (e.g., Robinne et al, at the global scale) to more complex assessments based on the probability of occurrence of both fire and the post‐fire contamination events (Langhans et al, ; Santos et al, ; Thompson et al, ). Advances in post‐fire erosion risk modelling (Neris et al, ; Robichaud et al, ) may serve to provide a foundation for more complex contamination models, but science advancements are still needed to support the development of these higher level predictive tools.…”
Section: The Framework In Practicementioning
confidence: 99%
“…For each case, the choice of contaminant(s) of concern and potential impacts constrain the possible approaches for post‐fire contamination assessment, and therefore, they should be identified at the outset. Recent studies have focused on determining the sensitivity to post‐fire contamination and range from relatively simple spatial indices (e.g., Robinne et al, at the global scale) to more complex assessments based on the probability of occurrence of both fire and the post‐fire contamination events (Langhans et al, ; Santos et al, ; Thompson et al, ). Advances in post‐fire erosion risk modelling (Neris et al, ; Robichaud et al, ) may serve to provide a foundation for more complex contamination models, but science advancements are still needed to support the development of these higher level predictive tools.…”
Section: The Framework In Practicementioning
confidence: 99%
“…FSim is a comprehensive fire occurrence, growth, behavior, and suppression simulation system that uses locally relevant fuel, weather, topography, and historical fire occurrence information to make a spatially resolved estimate of the contemporary likelihood and intensity of wildfire across the landscape [26]. Due to the highly varied nature of weather and fire occurrence across the large landscape, we ran FSim for each of the eight FOAs independently, and then compiled the 8 runs into a single coherent result using the method described in Thompson et al [27]. For each FOA, we parameterized and calibrated FSim based on the location of historical fire ignitions within the FOA, which is consistent with how the historical record is compiled.…”
Section: Wildfire Simulationmentioning
confidence: 99%
“…We combined the results into a single landscape-wide result where the area-wide burn probability is simply the sum of all eight FOAs, and flame-length probabilities are weighted by their respective FOA burn probability and summed across all FOAs as described in Thompson et al [27]. We then resampled the compiled 180 m results to a 90 m pixel size to match the resolution of the HVRA spatial layers.…”
Section: Wildfire Simulationmentioning
confidence: 99%
“…This is especially true in areas that are dependent on surface water coming from a highly fire-prone river basin. Regional studies from Thompson et al [12], Santos et al [54] and Moody and Martin [11], as well as reports from the U.S. Forest Service [9] and the Water Research Foundation [55] showed that wildfire risk in source watersheds raises concerns for water treatment and supply. The global information provided by our index might be a good way to identify regions across the planet showing higher levels of exposure, potentially requiring more detailed wildfire water risk analysis for regional water planning and management.…”
Section: The Gwwei and Its Implications For Water Resource Protectionmentioning
confidence: 99%
“…Although a significant number of studies have examined such second-order fire effects on surface freshwater resources [8], most have been conducted at a local or regional scale [8][9][10][11][12], whereas global-scale studies do not exist. Despite the ubiquitous nature of fire and the potential for adverse consequences on ecosystems and populations [13], large-scale assessments of the risks that fire can pose to water resources are lacking.…”
Section: Introductionmentioning
confidence: 99%